Low-temperature conversion of low-grade organic raw, part 1 (technical aspects) - Kazakov A. V. Aleksandr Vladimirovich; Tabakaev R. B. Roman Borisovich; Novoseltsev P. Yu. Pavel Yurievich; Astafyev A. V. Aleksandr Vladimirovich (2014, 2014)
Title screen